Traditional knowledge of wild edible plants with special emphasis on medicinal uses in Southern Shan State, Myanmar - Thant Shin; Kazumi Fujikawa; Aung Zaw Moe; Hiroshi Uchiyama (BMC, 2018)
Abstract Background Myanmar is one of the hotspots of biodiversity and is a rapidly developing country. Performing floristic research in Myanmar is an urgent issue, and ethnobotanical studies of wild edible plants (WEPs) will provide new information on natural plant resources. Method Ethnobotanical data were collected in three villages with different historical backgrounds in Southern Shan State, Myanmar. A total of 19 key informants were interviewed, and specimens were collected in the fields with the participation of key informants in June-July 2015. Group discussions were organized during 2016 and 2017 to reinforce the information on use of WEPs. DNA barcoding was used to facilitate species identification. Results A total of 83 species from 44 families of angiosperms were recorded as WEPs. Most of the species were used as wild vegetables (47 species), followed by fruits and nuts (31 species). Eighteen WEPs were consumed as medicinal foods. Differences in use of WEPs between the communities of the villages were observed. The age class of 30-39 years was more familiar with the environments where they could collect WEPs and had more knowledge of WEPs than did the older groups. The use of Elaeocarpus floribundus as an edible oil is a very interesting tradition. Conclusion WEPs play an important role in the livelihood of local communities. The indigenous society has maintained traditional knowledge of the WEPs. Historical background, land use system and surrounding vegetation could have effects on the variation in the traditional uses of WEPs. Increasing awareness of the importance of WEPs will encourage the conservation of traditional knowledge of indigenous populations.